Polymorphisms in VvPel associate with variation in berry texture and bunch size in the grapevine. (30th May 2013) - Vargas, A.M.; Fajardo, C.; Borrego, J.; De Andrés, M.T.; Ibáñez, J.
Abstract Background and Aims The identification of the genes involved in traits of interest is one of the main aims of current plant genetic studies. Although berry texture is a quality trait of great importance in table grapes, no quantitative trait loci or related gene has been described for this trait so far. Methods and Results In this work, the gene VvPel, which codes for a pectate lyase in the grapevine, was selected as a candidate gene for an association study. This gene was sequenced in a core collection of 96 table grape accessions, which was also characterised for several bunch and berry morphological traits, including diverse texture parameters measured by means of a texture meter. The population structure, the nucleotide and haplotype diversity, the protein structure, the existence of selection, and the linkage disequilibrium (LD) were evaluated. Thirty‐two single nucleotide polymorphisms (SNPs) and 15 haplotypes were identified in the VvPel sequence, and LD was low enough to provide a high‐resolution power. Some of the polymorphisms associated significantly with texture parameters and with bunch size, explaining part of the variation found for those traits. Conclusions Among the polymorphisms found in the gene VvPel, S1027 and S405/S441 in relation to berry texture, and S48/S1030 in relation to bunch size, are the most promising and would need to be investigated further as putative causal polymorphisms or markers for the respective traits. Significance of the Study The present work is the first genetic study on berry texture in the grapevine, and constitutes a starting point for a deeper understanding of the genetic basis of the natural variation for berry texture and bunch size.